FIGURE 2. Ceramaster patagonicus USNM 1122413. A. Abactinal surface. B in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 2. Ceramaster patagonicus USNM 1122413. A. Abactinal surface. B. (inset) Madreporite and close-up of abactinal plates. C. Lateral view-Superomarginal and inferomarginal plates (top series and bottom series respectively). D. Pedicellariae on marginal plates. E. Tube foot groove and furrow spines. F. Actinal surface. USNM 1121285. G. Penultimate superomarginals on smaller specimen. Scale Bar= 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 9, DOI: 10.5281/zenodo.276783